Strategies To Improve MSME Performance The Role Of Financial Literacy And Digital Financial Literacy (Study On Micro Businesses In Kediri City) - Nilawati, Oulivia; Setiawan, Doddy (Universitas Muhammadiyah Pontianak, 2025)
This investigation seeks to examine conventional financial competency impacts on small enterprise outcomes while evaluating technological financial knowledge intermediary functions among micro-business operators within Kediri Municipality. The research stems from growing requirements for small enterprises to accommodate electronic financial technology advancement, necessitating comprehension beyond traditional monetary elements to include technological components such as mobile payment systems, smartphone banking, and web-based credit services. The methodology employs numerical analysis utilizing pathway examination through Structural Equation Modeling Partial Least Square (SEM-PLS) frameworks. Research participants comprised 101 micro-business operators surveyed via Likert-format instruments. Findings demonstrated that conventional financial competency exerts beneficial and statistically significant immediate effects on both technological financial knowledge and small enterprise outcomes. Additionally, technological financial knowledge successfully functions as a significant intermediary between conventional financial competency and micro-business performance. These discoveries validate that enhancing fundamental monetary capabilities alongside comprehending electronic financial technologies can concurrently reinforce small enterprise competitive positioning and operational continuity within contemporary technological environments. The investigation offers actionable insights for governmental bodies and monetary institutions to broaden technological financial education initiatives as enhanced empowerment approaches for micro-enterprises.